A comparison of maternal anemia between HIV infected pregnant women receiving Zidovudine-based and Zidovudine-free highly active antiretroviral therapy (HAART) - Pattaramas Lertcheewakarn (2018)
Objective: To compare the prevalence of maternal anemia associated with usage of Zidovudine-free and Zidovudine-based HAART during pregnancy. Material and Method: A retrospective cohort study was conducted in HIV-infected pregnant women receiving HAART between January 2006 and December 2012 in Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Changes in hemoglobin levels were compared between zidovudine-free and zidovudine-based HAART groups. Results: Sixty-six pregnant women who received HAART, pre-exposure hemoglobin levels showed no significant difference between the zidovudine-free (14 cases) and the zidovudine-based (52 cases) groups. In non-anemic pregnant women before HAART initiation, the prevalence of post-exposure anemia was 40.5%, and similar in both groups. Post-exposure, decreased hemoglobin levels were greater in the zidovudine-based group (-1.46±0.64 g/dL) than the zidovudine-free group (-1.29±1.26 g/dL), but the difference was not significant (p = 0.766). Duration of the lowest post-exposure hemoglobin levels was shorter in the zidovudine-based group than the zidovudine-free group, but the difference was not significant (71.5 days and 105.6 days, p = 0.123). Conclusion: In almost half of the cases, both zidovudine-based and zidovudine-free HAART exposure was associated with substantial risk of maternal anemia during pregnancy. Pregnant women receiving HAART regimens may be at significant risk of anemia two to three months after exposure and should be adequately monitored for this complication.